Revit 2017 Essential Training: MEP (Imperial). - Wing, Eric (linkedin.com, 2016)
Learn about MEP design. Explore four major trades of MEP engineering: mechanical, electrical, plumbing, and fire protection by reviewing examples imperial units, (inches and feet).